LEARNING VOCABULARY THROUGH GAMES: A CRITICAL REVIEW - Fatimah Fatimah; Harits Masduqi (EDUCAFL : Journal of Education of English as Foreign Language, 2021)
For decades linguists have been interested in doing research on English vocabulary and vocabulary teaching. In the article Learning Vocabulary through Games published in the Asian EFL Journal, Huyen and Nga investigate the benefits of using games for their students’ vocabulary learning. They argue that games are helpful for students to enrich their English vocabulary acquisition. As of May 2021, the article has been quite influential and cited for 381 times by scholars and students around the world. This paper presents a critical review of the aforementioned article. The discussion is mainly centred on the relation between the research and communicative language teaching, strengths and weaknesses of the research, and reflection of the research findings on the authors’ learning and teaching experience.